PIDS Annual Macroeconometric Model 2000 - Josef T. Yap (Philippine Institute for Development Studies (PIDS), 2000)
The basic framework of the PIDS Annual Macroeconometric Model is presented in this paper. After outlining the general philosophy of the model, the discussion focuses on the production sector of the model in order to trace the manner by which macroeconomic policies affect relative prices and sectoral allocation of resources. The theoretical framework is largely derived from Constantino, Yap, Butiong and dela Paz (1990a, 1990b). The details of the PIDS-NEDA model are reported in these references while the most recent reestimation is presented in Reyes and Yap (1993). A section in the main text lists the major changes that are introduced in the 2000 version of the model.
Keywords: 330; economic/development modelling; Makroökonometrie; Wirtschaftspolitik; Industrieproduktion; Philippinen